Bending and Torsional Characteristics of Carbon Fiber and Balsa Wood Sandwich Composite - Astasari Astasari; Sutikno Sutikno; Wahyu Wijanarko (IPTEK Journal of Proceedings Series, 2017)
Bending properties and torsional stiffness of carbon fiber woven and balsa wood sandwich composites are studied and presented in this paper. Three point bending and torsional responses are tested with finite element’s software. The finite element method was employed to determine applied load, total deformation, and equivalent stress of sandwich beam with different number of carbon fiber woven layer and orientation. In this study, variations of adjustment layers with 3 types of fiber orientation (0o, 45o, 60o). The result indicated that adding more carbon fiber layer could improve mechanical properties for sandwich beam.